Evaluation in Japan - Ryo Sasaki (The Evaluation Center at Western Michigan University, 2005)
Two years have passed since the "Government Policy Evaluations Act" (GPEA) became effective in Japan on April 1, 2002. In that time, evaluation has been well accepted as an essential part of the policy management cycle at each ministry of the Japanese government. It is reported that evaluation results have been utilized for budget formulation by governmental ministries, and it is also observed that policies have been prioritized and, conversely, abolished based on the evaluation results. Other merits of introducing evaluation are that the so-called 'policydiagram' has been frequently developed at ministries, and policy goals havebecome more outcome-oriented with more quantitative measures. Now the Act is under discussion for amendment with some major points proposed for change.